FENOMENA MENIKAH DI KALANGAN MAHASISWA FISIP UNIVERSITAS RIAU (Studi Fenomenologi Tentang Motif, Makna dan Pengalaman Komunikasi) - Sindi Faradilla; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the rise of the phenomenon of marriage among students. Making the decision to get married while in college certainly has gone through many considerations. They must be confronted with conditions where they are required to be able to manage their time, energy, and mind to take care of the family but not neglect their academic activities. This requires emotional maturity and good self-management to carry out both roles; as students and as husband / wife. This study aims to determine the motives, meanings and experiences of marriage for FISIP students of Riau University.This research uses a qualitative research method with a phenomenological approach. Data collection techniques consist of in-depth interviews, observation and documentation. The gathering of informants in this study used a purposive technique with the number of research informants as many as eight (8) people consisting of married students of FISIP Riau University. Data analysis techniques were obtained using data collection, data reduction, data display, and decision making and verification.The results of this study indicate that the motive was married among students FISIP is two Because to motive that consists of losing the figure of the father, avoiding the sins of courtship, and love. Whereas in order to motive consists of building a happy family, and wanting a guaranteed life. Then, the meaning of marriage among FISIP students is to emigrate, lifelong cooperation, a new phase for learning, and promise engagement. Communication experience is divided into pleasant (positive) communication experience which consists of finding a life partner, a new life spirit, and the spirit of completing college. Furthermore, an unpleasant (negative) communication experience consists of getting negative comments, difficulty managing time, not being free, conflicting, and disturbed health. Keyword : marriage, communication experience, students